Endovascular Treatment of Complex Vascular Diseases of the Internal Carotid Artery Using the Willis Covered Stent: Preliminary Experience and Technical Considerations - Ma, Lin; Feng, Hao; Yan, Shuo; Xu, Ji-Chong; Tan, Hua-Qiao; Fang, Chun (Frontiers in Neurology, 2020)
Purpose: The Willis covered stent (WCS) is used to treat complex vascular diseases of the internal carotid artery; however, its performance requires further investigation. This study aimed to present our single-center clinical results and experience of endovascular repair of complex vascular diseases of the internal carotid artery using the WCS. Methods: Patients who presented with complex vascular diseases of the internal carotid artery and who were treated with the WCS from December 2013 to September 2018 were retrospectively reviewed. Procedural results, perioperative complications, incidence of endoleak, and follow-up outcomes were analyzed. Results: Sixty-five patients were enrolled. A total of 25 large aneurysms, 10 pseudoaneurysms, 14 blood blister-like aneurysms, 11 carotid–cavernous fistulas, and 5 surgical injuries were assessed. WCS placement was successful in all patients. Immediate angiography showed that complete repair of the target artery was achieved in 56 patients (86.2%). Endoleak was observed in nine patients, including seven type I endoleaks and two type II endoleaks. Occlusion of a side branch vessel occurred in four patients. Acute in-stent thrombosis occurred in one patient. No ischemic or hemorrhagic events or other complications developed during the perioperative and follow-up periods. Angiographic follow up (mean duration, 12 ± 3.29 months) was performed in 60 patients and showed complete target artery repair in 58 patients, and asymptomatic mild-to-moderate in-stent stenosis was observed in four patients. Slight endoleak persisted in two patients without enlargement or rupture of the residual lumen. Conclusion: WCS implantation is safe, feasible, and efficacious for endovascular repair in patients with complex vascular diseases of the internal carotid artery, showing excellent short-term target artery patency and clinical outcomes.